Pesticide Toxicity Profile: Synthetic Pyrethroid Pesticides - Frederick M. Fishel (EDIS)
This document provides a general overview of human toxicity, provides a listing of laboratory animal and wildlife toxicities and a cross reference of chemical and common names with their trade names of many synthetic pyrethroid pesticides registered for use in Florida. This document is PI-54, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published July, 2005.